Developing Animated Videos as Islamic Religious Education Learning Media - Hasriadi, Hasriadi; Yamin, Muh.; Fakhrunnisa, Nur; Mutmainna, Mutmainna; Pamessangi, Andi Arif (Universitas Pendidikan Indonesia, 2025)
This study aims to develop Islamic Education learning media using animated videos for elementary school students. The objectives are to: (1) identify the development stages of an animated video themed on sincerity for fifth-grade students; (2) evaluate its validity; and (3) assess its practicality in classroom use. The research employed a Research and Development (RD) approach using the ADDIE model. The study involved Islamic Education teachers and fifth-grade students. Data were collected through observations, interviews, and questionnaires for expert validators, teachers, and students, as well as documentation. The results indicate that the animated video was developed in accordance with the ADDIE stages. The analysis revealed limited use of instructional media. In the design and development phases, materials were prepared, and the video was produced. It was then validated by experts and tested by users. The media was rated highly valid with a score of 89.15%, and its practicality was rated at 94.5% based on feedback from teachers and students. These findings suggest that the media has strong potential as a practical learning tool. It is recommended that teachers receive training in instructional media development and that animated videos be effectively integrated into the curriculum. Future studies should investigate broader applications and the long-term effects on student learning outcomes.